DETERMINANTS OF INTEGRATED ANTENATAL CARE VISITS PARTICIPANTS OF THE NATIONAL HEALTH INSURANCE PROGRAM AT JAMBI CITY HEALTH CENTER - Nadapdap, Ivanna Tiur Nauli; Dwi Noerjoedianto; Adila Solida; Guspianto Guspianto (Pusat Riset dan Inovasi Nasional, 2023)
Background: Integrated Antenatal Care (ANC) is a comprehensive service effort for pregnant women in the early detection of complications of pregnancy whose scope of visits has the aim that pregnant women can have a positive experience in undergoing pregnancy and childbirth. The government presents the JKN program for pregnant women with the aim of reducing costs in obtaining services, so as to reduce MMR. In Jambi City, there are still several health centers that have not met the target of the coverage of Integrated ANC visits. The purpose of this study was to determine the determinants of integrated ANC visits to participants in the National Health Insurance program at the Jambi City Health Center in 2022. Methods: This study used a quantitative research type with a descriptive approach and a cross sectional design. The data were obtained from a sample of 103 pregnant women respondents at the Jambi City Health Center, the research variables consisted of knowledge, education, employment, income, husband's support and support from health workers. The sampling technique uses proportional random sampling. Results: Bivariate analysis using the Chi-Square test found that factors related to integrated ANC visits were knowledge (0.006), occupation (0.001), income (0.01), husband's support (0.001), health worker support (0.000). There is no educational relationship (0.47). Conclusion: Variables that have a relationship are knowledge, work, income, husband's support, and support from health workers, while education does not.